Pemberdayaan Masyarakat Pesisir Melalui Pengembangan Sumber Daya Laut (SDL) Dalam Meningkatkan Perekonomian masyarakat Desa Branta Pesisir Kecamatan Tlanakan Kabupaten Pamekasan - Imadoeddin Imadoeddin; Syaiful Syaiful; Rini Aristin; Syaiful Anam; Anisa Fajriana Oktasari (COVIT (Community Service of Health), 2022)
The mandate of Law Number 27 concerning the management of coastal areas is the government's representation for coastal communities to develop the potential of Natural Resources and Human Resources (NR and HR).Through its enormous marine potential, it should provide hope and opportunity, especially for coastal communities to become prosperous communities. So with such a large marine wealth, it seems unbelievable that it has not been able to prosper the lives of the fishing community. Most Indonesian fishermen still live within the poverty line. The poor criteria are shown by the low income of fishermen, so that they still experience difficulties in meeting their basic needs for food, clothing, health, housing and a decent level of education.In order to realize a prosperous coastal community, creativity and innovation are needed to encourage and maintain food security so as to provide effective solutions for poverty alleviation in the village of Branta Pesisir, Tlanakan District, Pamekasan Regency. Keywords: Coastal Community Empowerment, Natural Resources and Human Resources, Community Economy